ℵ1-A-coseperable groups - ALBRECHT, Ulrich (Studia Universitatis Babeș-Bolyai Mathematica, 2015)
Let A be a countable self-small Abelian group with a right Noetherian right hereditary endomorphism ring. We show that the question whether strongly-ℵ1-A-generated groups are ℵ1-A-coseparable is undecidable in ZFC. Our main focus is on the algebraic aspect of the proof, not on the underlying set-theory. Mathematics Subject Classification (2010): 20K20, 20K40.